Pendampingan Kelompok Tanggap Bencana dengan Pendekatan Fikih Kebencanaan Sebagai Mitigasi Bencana Alam di Desa Batu Beriga, Kabupaten Bangka Tengah - Desfa Yusmaliana; Fadillah Sabri; Fifin Fitriana (Universitas Mathla'ul Anwar Banten, 2022)
Bangka Island is a tin mining area and has the potential for natural disasters due to these mining activities such as drought, erosion, and sedimentation disasters. The Islamic perspective must be contemplated further to understand and address every incident proportionally in interpreting and responding to disasters. The Tarjih Council and Tajdid Muhammadiyah have formulated disaster fiqh that must be conveyed, primarily through youth organizations consisting of the youth of the nation's generation as part of the service program. Furthermore, these youth groups are referred to as